Functional brain network centrality is related to APOE genotype in cognitively normal elderly. Issue 9 (22nd August 2018) - Wink, Alle Meije; Tijms, Betty M.; ten Kate, Mara; Raspor, Eva; de Munck, Jan C.; Altena, Ellemarije; Ecay‐Torres, Mirian; Clerigue, Montserrat; Estanga, Ainara; Garcia‐Sebastian, Maite; Izagirre, Andrea; Martinez‐Lage Alvarez, Pablo; et al.
Abstract: Introduction: Amyloid plaque deposition in the brain is an early pathological change in Alzheimer's disease (AD), causing disrupted synaptic connections. Brain network disruptions in AD have been demonstrated with eigenvector centrality (EC), a measure that identifies central regions within networks. Carrying an apolipoprotein (APOE)‐ε4 allele is a genetic risk for AD, associated with increased amyloid deposition. We studied whether APOE‐ε4 carriership is associated with EC disruptions in cognitively normal individuals. Methods: A total of 261 healthy middle‐aged to older adults (mean age 56.6 years) were divided into high‐risk (APOE‐ε4 carriers) and low‐risk (noncarriers) groups. EC was computed from resting‐state functional MRI data. Clusters of between‐group differences were assessed with a permutation‐based method. Correlations between cluster mean EC with brain volume, CSF biomarkers, and psychological test scores were assessed. Results: Decreased EC in the visual cortex was associated with APOE‐ε4 carriership, a genetic risk factor for AD. EC differences were correlated with age, CSF amyloid levels, and scores on the trail‐making and 15‐object recognition tests. Conclusion: Our findings suggest that the APOE‐ε4 genotype affects brain connectivity in regions previously found to be abnormal in AD as a sign of very early disease‐related pathology. These differences were too subtle in healthy elderly to use EC for single‐subject prediction of APOE genotype. Abstract : Decreased functional brain eigenvector centrality measured from fMRI was associated with APOE genotype, a genetic risk factor for Alzheimer's disease. Changes were found in the visual cortex, posterior cingulate, and precuneus.